The fate of acetic acid during glucose co-metabolism by the spoilage yeast Zygosaccharomyces bailii - Rodrigues, Fernando José dos Santos (2012)
Zygosaccharomyces bailii is one of the most widely represented spoilage yeast species, being able to metabolise acetic acid in the presence of glucose. To clarify whether simultaneous utilisation of the two substrates affects growth efficiency, we examined growth in single- and mixed-substrate cultures with glucose and acetic acid. Our findings indicate that the biomass yield in the first phase of growth is the result of the weighted sum of the respective biomass yields on single-substrate medium, supporting the conclusion that biomass yield on each substrate is not affected by the presence of the other at pH 3.0 and 5.0, at least for the substrate concentrations examined. In vivo(13)C-NMR spectroscopy studies showed that the gluconeogenic pathway is not operational and that [2-(13)C]acetate is metabolised via the Krebs cycle leading to the production of glutamate labelled on C(2), C(3) and C(4). The incorporation of [U-(14)C]acetate in the cellular constituents resulted mainly in the labelling of the protein and lipid pools 51.5% and 31.5%, respectively. Overall, our data establish that glucose is metabolised primarily through the glycolytic pathway, and acetic acid is used as an additional source of acetyl-CoA both for lipid synthesis and the Krebs cycle. This study provides useful clues for the design of new strategies aimed at overcoming yeast spoilage in acidic, sugar-containing food environments. Moreover, the elucidation of the molecular basis underlying the resistance phenotype of Z. bailii to acetic acid will have a potential impact on the improvement of the performance of S. cerevisiae industrial strains often exposed to acetic acid stress conditions, such as in wine and bioethanol production.